Assessment of Regulating Ecosystem Services of Buner watershed - Zeeshan, Muhammad; Saleem, Aamir; Haider, Asim; Haq, Mian Armaghan ul; Sajawal, Muhammad; Sultan, Zain (Journal of Agriculture and Biology, 2025)
A watershed is a land area that drains into a river, lake, or ocean. Forests play a crucial role in maintaining watershed health by acting as natural filters, trapping contaminants, stabilizing soil, reducing sedimentation and erosion, and controlling water quality. A research site is the Buner Watershed located in Khyber Pakhtunkhwa, Pakistan, known to have complex, variable, and potentially problematic mountain terrain for water management, sediment deposition, and soil erosion issues. The study aimed to highlight on how soil stabilization, water flow regulation and improved water quality can all be achieved through forest conservation and management. comparable areas with hydrological and environmental issues. Comparatively, comparable areas are those that host similar hydrological and environmental circumstances. This comprehensible assessment has stressed upon the major role that forests have with respect to the sustenance of this Buner Watershed health and functionality. Water quality and erosion control were taken into consideration in the Research study. Two sites, i.e. Vegetative and non-vegetative were selected for sample collection. Physical parameters like temperature, turbidity and TSS were taken for statistical analysis. Data collected were comparatively analyzed using statical tests which shows that the vegetated site generally shows better water quality parameters, which is consistent with the expectations of reduced turbidity, temperature, and sediment in vegetated environments. The non-vegetated site shows higher turbidity, temperature, and TSS, which might indicate issues such as erosion or lack of vegetation management. Both the sites were comparatively analyzed and from the results we would recommend that it is crucial to prioritize the conservation of existing forests to protect against soil erosion by implementing policies that prevent deforestation and degradation, ensuring that forested areas remain intact.
Keywords: Watershed Management; Regulating Ecosystem Services; Water Quality; Soil Erosion; Forest Ecosystem Services; Total Suspended Solids (TSS); Sedimentation